Risk and return on long-lived tangible assets - Schmalensee, Richard (Journal of Financial Economics, 1981)
Assuming rational expectations, a specialization of Ross' Arbitrage Pricing Theory is used to obtain a simple securities market valuation formula when dividends follow linear stochastic processes. The implications of this model for the use of accounting data to measure risk and for capital budgeting are explored. A new measure of riskiness based on accounting data is derived, and the use of risk-adjusted discount rates is evaluated.